Work-related musculoskeletal disorders: prevalence, associated factors, and impact on quality of life among kitchen workers in hospitality industry, Bahir Dar City, Northwest Ethiopia, 2023 - Abebaw, Tadiwos; Destaw, Bikes; Yenealem, Dawit Getachew; Tesfaye, Amensisa Hailu; Melaku, Christian; Mamaye, Yimer; Bezie, Anmut Endalkachew; Abere, Giziew (Frontiers in Public Health, 2024)
Introduction Work-related musculoskeletal disorders (WMSDs) are considered major public health problems globally, deteriorating the quality of life of workers in various occupations. Kitchen work is reported as among the occupations most prone to these maladies. Nevertheless, prevalence of WMSDs, contributing factors, and impacts on the quality of life of hospitality industry kitchen workers are insufficiently documented in Ethiopia. Therefore, this study aimed to assess the prevalence of WMSDs, their associated factors, and impact on the quality of life of hospitality industry kitchen workers in Bahir Dar city, Ethiopia. Methods An institution-based, cross-sectional study was conducted from 17 April to 17 May 2023. A total of 422 participants were included using a simple random sampling technique. WMSDs were evaluated using an interviewer-administered Nordic standardized questionnaire. The short form-36 questionnaire was used to assess quality of life. The data were collected using the Kobo tool box. SPSS version 26 software was used to perform both bivariable and multivariable binary logistic regression analyses. Independent t-tests were used to show the impact of WMSDs on quality of life scales across groups with and without WMSD symptoms. Result In this study, the response rate was 98.34% (n = 415). The 1-year prevalence of WMSDs among kitchen workers was 82.7% [95% CI: (79.1, 86.3)]. Age group between 30 and 39 years [AOR: 2.81; 95% CI: (1.46–5.41)], job dissatisfaction [AOR: 2.45; 95% CI: (1.34–4.45)], anxiety [AOR: 2.26; 95% CI: (1.12–4.52)], prolonged standing [AOR: 3.81; 95% CI: (1.58–9.17)], and arm overreaching [AOR: 2.43; 95% CI: (1.34–4.41)] were significantly associated factors with work-related musculoskeletal disorders. Work-related musculoskeletal disorders had a significant impact on all quality of life dimensions, in which the mean SF-36 scores of participants with WMSDs were lower than those of their non-WMSD counterparts. Conclusion This study revealed that the prevalence of WMSDs was relatively high. Age between 30 and 39 years, job dissatisfaction, anxiety, prolonged standing, and arm overreaching were identified as significant determinants of WMSDs among kitchen workers in hospitality industries. The presence of one or multiple WMSDs, in turn, is associated with worse quality of life dimensions of individuals.